High-resolution adaptive optical imaging within thick scattering media using closed-loop accumulation of single scattering - Sungsam Kang (Nature Portfolio, 2017)
Optical imaging deep in biological tissue is difficult due to multiple scattering and specimen induced aberrations of both the incident and reflected light. Here, Kang et al. develop an adaptive closed-loop algorithm to correct tissue aberrations in the presence of multiple scattering for deep tissue imaging.